Building the Competitiveness of Sarabba Drink Sellers Based on Competitive Advantage in Makassar City - Tafsir, Muhammad; Tamsil, Iqbal; Syahid P, Rahman; Amran, M. Adharry Dwiki Syaputra; Lamato, Riski M. (INOVASI, 2024)
This study employs a phenomenological approach as a qualitative research method. The findings indicate that Sarabba, a traditional drink unique to Makassar, stands out for its distinctive taste and health benefits, as well as its strong cultural significance. The drink holds significant potential for growth and popularity, both among locals and tourists, due to its cultural relevance and beneficial properties. By implementing the appropriate marketing strategies, driving product innovation, and fostering cross-sector collaboration, Sarabba has the potential to expand its reach beyond the local community. With these efforts, the drink could revive interest across the nation, creating a broader appreciation for its cultural heritage and health benefits. This research highlights how leveraging the unique attributes of Sarabba, in combination with modern business practices, could enhance its competitiveness in the market, enabling it to thrive in an increasingly globalized world. Through such initiatives, the potential for Sarabba to become a widely recognized and cherished product both locally and nationally is substantial. The study underscores the importance of strategic marketing, innovation, and collaboration in preserving and promoting local traditions while ensuring business success.